Business Groups and Herding Behavior During the Covid-19 Pandemic - Espinosa-Mendez, C (Faculty of Social Sciences, 2022)
This article studies whether herding behavior is present in stock returns of business groups during the COVID-19 pandemic in Latin American Integrated Market (MILA), composed by Chile, Colombia, Mexico, and Peru. Using the series of daily prices and daily traded volumes of the shares of the companies affiliated with a business group and that are included in the stock market indices S&P/IPSA (Chile), COLCAP (Colombia), IPC (Mexico) and S&P/BVL (Peru), from January 1, 2010 to October 27, 2021, with the exception of Mexico, we observe herding behavior during COVID-19 in businesses affiliated with business groups in MILA. In addition, from May 2020 onwards, stock behavior shifts to reverse herding. This study also reports that when the market is up herding is stronger during COVID-19. Something similar occurs for low market volatility and low volume of trading. © 2022, Faculty of Social Sciences. All rights reserved.